Charge Renormalization, Thermodynamics, and Structure of Deionized Colloidal Suspensions (Communications in Computational Physics, 2018)
In charge-stabilized colloidal suspensions, highly charged macroions,dressed by strongly correlated counterions, carry an effective charge that can be substantiallyreduced (renormalized) from the bare charge. Interactions between dressedmacroions are screened by weakly correlated counterions and salt ions. Thermodynamicand structural properties of colloidal suspensions depend sensitively on themagnitudes of both the effective charge and the effective screening constant. Combininga charge renormalization theory of effective electrostatic interactions with MonteCarlo simulations of a one-component model, we compute osmotic pressures and pairdistribution functions of deionized colloidal suspensions. This computationally practicalapproach yields close agreement with corresponding results from large-scale simulationsof the primitive model up to modest electrostatic coupling strengths.